2017
DOI: 10.1044/2016_ajslp-15-0069
|View full text |Cite
|
Sign up to set email alerts
|

Effective Team Practices: Interprofessional Contributions to Communication Issues With a Parent's Perspective

Abstract: Building teams with IPCP can be effective for including families and creating high-quality outcomes for individuals with severe disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…[52][53][54][55][56][57] The remaining 13 included articles were discussion articles or reviews. 8,9,[58][59][60][61][62][63][64][65][66][67][68] The results of the review are presented according to the objectives of the review:…”
Section: Resultsmentioning
confidence: 99%
“…[52][53][54][55][56][57] The remaining 13 included articles were discussion articles or reviews. 8,9,[58][59][60][61][62][63][64][65][66][67][68] The results of the review are presented according to the objectives of the review:…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has introduced different models and practices that can be used to balance the power structures of the participants' roles in educational decision-making, and could thus be used in the IEP process for pupils with the AACM or PIMD. These include a shared leadership model [33,67] and building teams with interprofessional collaborative practice [47].…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, the findings of those few studies that concentrated on the IEP goal-setting process for pupils with PIMD have shown that IEP teams' collaboration can be problematic, and various elements, such as the structure of IEP meetings and communication prior to the actual meeting, can influence the decisions; see [31,32,47]. Therefore, research is needed about the multi-professional teams' structure considering pupils with the AACM and how their individual goals are formed in the collaborative decision-making process.…”
Section: Setting Goals For Pupils With Profound Intellectual and Multiple Disabilitiesmentioning
confidence: 99%
“…It creates opportunities for learning other perspectives, supports goal setting, focuses on efficiency and effectiveness in service delivery, clarifies roles and responsibilities, builds on relationships, and requires accountability. 11 It is, however, not without implementation challenges.…”
Section: Strengths Of An Interprofessional Collaborative Practice Modmentioning
confidence: 99%